The Social Capital in The Disaster Mitigation of The Forest and The Peatland Fire in Bengkalis Regency, Riau Province - Yesi Yesi; Jalil Ashaluddin; Ling Chan Kim; Asriwandari Hesti; Hidir Achmad; Sugiyanto Seger (E3S Web of Conferences)
The fires of the forest and the peatland are serious environmental threats. In addition to damaging ecosystems, these fires also cause extensive health, social, and economic impacts. In the middle of the mitigation efforts, the social capital plays an important role in strengthening the capacity of the local communities to prevent and deal with these disasters. This study aims to explore the role of the social capital in the forest and the peatland fire mitigation using a qualitative approach. The case study was implemented in Tanjung Belit Village, Bengkalis, involving in-depth interviews with the local stakeholders, such as the Disaster Care Community (MPB), the local communities, and the local government. The results of the study indicate that the social capital in the form of the trust, the shared norms, and the social networks are the key elements in driving the collective action and increasing the effectiveness of mitigation programs. The active involvement of local communities, the understanding of the local wisdom, and the synergy between actors are the main drivers of the prevention efforts success of the forest and the peatland fire. This study concludes that the strengthening social capital is an important strategy that must be prioritized in community-based disaster mitigation policies to achieve environmental sustainability.